Measurement of rational thinking skills in people affected by annual floods - I Gusti Ayu Agung Noviekayati; Djoko Budi Utomo; Herlan Pratikto (Fakultas Ilmu Pendidikan)
Disaster is an unplanned event with great physical and psychological effects. The ability of communities to cope with disasters varies greatly. Starting from the ability to think simple about disasters to critical strategic thinking skills. Research on the ability to think rationally at the time of disaster is still very little. This is due to the concentration of research on disasters aimed at mitigation and post-disaster that are physical, emotional and behavioral. Research on rational decisions has been researched for purposes such as management, politics, sustainable energy, education. In the field of psychology, rational decisions are examined in industry and organizations. Examining this rational decision needed in the field of disaster is to reduce vulnerability to become victims in disaster areas.